Pemberdayaan Ekonomi Rumah Tangga melalui Pemanfaatan Apotek Hidup sebagai Upaya Penghematan dan Ketahanan Kesehatan Masyarakat Desa Bangun Purba - Ginting, Edi Suranta; Husein, Ismail (Civiliza Publishing, 2026)
This community service program, conducted through the Community Service Program (KKN), aims to support household economic empowerment and community health resilience in Bangun Purba Village through the creation of a living pharmacy. A living pharmacy is the use of land for the cultivation of family medicinal plants that can be used as an alternative to simple treatments and for health promotion and prevention. The program begins with coordination and obtaining permits from the village government, followed by land provision, site preparation, and the planting of family medicinal plants by KKN students. As a form of indirect education, information media is provided in the form of brochures containing the names and benefits of medicinal plants that are laminated and attached directly to each plant. The results of the program implementation indicate that the living pharmacy has the potential to provide benefits to the community, both in terms of health and household economics, particularly in reducing dependence on modern medicines for minor health needs. In addition, the existence of information media on medicinal plants supports the independent and sustainable increase in community knowledge. However, this program faces several challenges, such as limited time for KKN implementation and the sustainability of plant care. Overall, the creation of a living pharmacy is a form of community service that is applicable and relevant to the village's needs.